Differences In The Use Of IT Infrastructure Among Business Enterprises Operating In The Visegrád Group Of Countries - Attila Jóczik; Péter Sasvári (CEEeGov Days 2014, eGovernment: Driver or stumbling block for European integration? Proceedings of the CEEeGov Days, May 8-9, 2014, Budapest, 2014)
The aim of using information technology and information systems is to improve the efficiency and effectiveness of economic activities. Examined by their size categories, the enterprises operating in the Visegrád group of countries produce different average added value, which can also be detected in their use of IT infrastructure. In comparison to their Visegrád peers, micro-enterprises in Slovakia, small-sized businesses in Poland, medium-sized enterprises in the Czech Republic and corporations in Hungary produced the highest added value on average, which is closely related to the usage of IT infrastructure in those countries. It also follows that various business information systems can be found at the small- and mediumsized enterprises in the Czech Republic and Poland in the largest proportion. These systems were applied by Hungarian and Slovakian small- and medium-sized enterprises at the lowest frequency rate. Personnel responsible for the operation of IT functions at micro- and smallsized enterprises vary from country to country, an employee working at a lower position was entrusted with this task in the Czech Republic and Slovakia, while IT managers in Hungary and external specialists in Poland were in charge of the operation of IT infrastructure. Corporations tended to entrust IT managers with this task in each of the studied countries.
Keywords: M13; M15; 330; IT Infrastructure; Visegrád Group Of Countries; Hungary; the Czech Republic; Slovakia; Poland